Role of iron-binding organic ligands in the distribution of dissolved iron in Antarctic sea ice - Genovese, C (2021)
The availability of iron (Fe) is decisive for biochemical reactions involved in marine primary productivity and atmospheric carbon dioxide drawdown. Low Fe solubility and paucity of Fe sources lead to Fe limitation in Antarctic surface waters, which strongly constrains phytoplankton growth. This limitation is seasonally alleviated when sea ice melts, as sea ice is generally enriched in Fe compared to seawater. This natural fertilization event benefits both sympagic ice algae and pelagic phytoplankton. In seawater, the concentration of dissolved Fe (DFe) is controlled by iron-binding organic ligands (L), yet sea-ice environment is comparatively understudied. The first part of this thesis (Chapter 2) aimed to investigate how salinity and temperature may affect the physicochemical detection of L. The experimental design offered a comparison between artificial ligands used in sea-ice samples (1-nitroso-2-naphthol or NN) and in seawater samples (salicylaldoxime or SA, and 2-(2-thiazolylazo)-p-cresol or TAC), in order to define: 1) which artificial ligand is more appropriate for the determination of L in the sea-ice environment; 2) the fertilization potential of sea ice, with respect to L, allowing the comparison between sea-ice and seawater data. Within the salinity range considered (1 < S < 90), only SA and NN were successfully calibrated, whereas conditional stability constants were not achieved with TAC outside the 21 < S < 35 range. When titrating natural samples, only SA was able to detect DFe organic speciation parameters along the salinity range considered (5 < S < 78). The results, therefore, suggest that SA is the most suitable artificial ligand for the investigation of L in sea ice. In addition, a second experiment was performed, to understand if the common practice of titrating samples at room temperature, instead of at in-situ conditions, can affect the determination of the DFe complexing parameters. The titration of natural samples with both NN and SA at different temperatures (4 ¬¨‚à´C ...